How personality traits influence impulsive buying through the sequential mediation of family dynamics and self control - Pei Xie; ChaoZheng Huang; Tianwei Xu; Jiawei Cui (Scientific Reports)
Abstract The present investigates how personality traits influence impulsive buying (IB) among college students, emphasizing the mediating effects of family dynamics and self-control. Using a structural equation model, we analyzed responses from 578 college students in Gansu Province, China to explore the relationship between the Big Five personality traits, family dynamics, self-control, and IB tendencies. Neuroticism and extroversion are positively associated with IB, whereas conscientiousness is negatively associated with it. Family dynamics and self-control significantly mediate the relationship between personality traits and IB. This study reveals the complex interplay between individual personality traits and external factors in IB, and suggests a focus on family-specific and self-regulatory interventions. The findings provide educators and policymakers with practical strategies aimed at strengthening family relationships and self-control to curb IB behavior among youth. Furthermore, this study offers a novel perspective on IB by integrating personality traits, family dynamics, and self-control, thereby contributing valuable insights to the literature on consumer behavior as well as strategies to mitigate financial risk among young consumers.